Dynamic boundaries of acceptable play: a mixed methods examination into players' interpretations of toxic behavior in multiplayer online games - Yu, Valerie Jingwen (Nanyang Technological University, 2024)
Scholarship on toxic behavior in multiplayer online games has largely focused on examining its causes and effects. However, there has been less work on defining the concept—for example, what it means and entails. This has been somewhat problematic for understanding the range of toxic behavior that current findings apply to and whether players interpret the presented examples of toxic behavior as intended. In this dissertation, I aimed to narrow the gap relating to these issues by conducting a series of sequential mixed-methods studies. These studies unraveled players’ understanding of the term toxic behavior and the dynamic nuances pertinent to their recognition and interpretation of others’ behavior as toxic in multiplayer online games. From player interviews in the first study, I derived the definition of toxic behavior in multiplayer online games to be "socially undesirable and intentional actions causing fellow players to experience detrimental effects." I also proposed a typology of toxic behavior based on players’ experiences shared during the interviews. However, I found that players' practical interpretations of social behavior as toxic in multiplayer online games involved elements of intuition and subjectivity depending on contextual considerations. When faced with actual gaming scenarios, players’ subjective recognition of toxic behavior sometimes departed from their objective, out-of-game descriptions of what they believed game-based toxicity to be. This study unraveled how players may undergo dynamic and potentially skewed interpretations towards different types of toxic behavior depending on their individual dispositions, the social context, and the gameplay setting. I extended the proposed typology through a review and reorganization of prior categorizations to include two additional types of toxic behavior that were not covered by interviewees in the first study. Then, in the second study, I utilized the proposed typology to examine the patterns in players’ Reddit discussions of toxic behavior experienced in multiplayer online games. This analysis found that identity-related offensive expressions, game-based offensive expressions, and gameplay sabotage were the most frequently discussed types across both competitive and cooperative games. In the third study, a controlled experiment examined player interpretations of gameplay sabotage in greater detail, through gameplay scenarios within League of Legends. I found that players' negative perceptions and responses when encountering gameplay sabotage were exacerbated in more competitive gameplay settings. At the same time, more competitive gameplay settings may also drive stricter thresholds when determining acceptable behavior, even in interactions where overt toxicity is absent. This dissertation enhances scholarly understanding of toxic behavior in MOGs from the perspective of gamers. It presents novel findings about how gamers define toxic behavior in MOGs, the types of toxic behavior gamers experience in MOGs, and the interpretive processes they undergo to recognize and assess toxic behavior when playing MOGs. Its insights can also be extended to develop clearer definitions and typologies of toxic behavior in other online social spaces. Future research can also extend these findings by examining a wider range of factors that might influence interpretations of toxic behavior when playing MOGs. With clearer definitions and an understanding of how players’ recognition of toxic behavior can shift based on subjective interpretations of an interaction, findings relating to toxic perpetration and its impact can be better contextualized and utilized to develop more effective interventions to discourage toxicity.